The Architect's Legal Responsibility for Design Errors That Result in Material Loss to the Building Owner - Nathalia, Yenny; Sitompul, Roswita; Isnanul, OK (International Journal of Business, Law, and Education, 2025)
An architect is responsible for the building and the safe use of the building. The responsibility of an architect is not only limited to civil matters but also criminally liable if proven to have committed negligence or negligence that causes building construction errors. The legal research method used in this research is normative juridical research which is research conducted or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object under study. The data source used is secondary data with quantitative data analysis. The result of this research is the Implementation of Architect Performance Standard regulated in Law No. 6 Year 2017 About, Legal Position of Architect as Building Development Planner based on Law No. 2 Year 2017 About Construction Service is as Construction service provider who has special expertise in implementing construction service while according to Architect Law, Architect Obstacle as Building Development Planner is non-technical obstacle and technical obstacle.